A new species of genus Schistura from Pumat national park, Nghean province, Vietnam - Kho, Nguyen Xuan; Duc, Nguyen Huu (Academia Journal of Biology, 2014)
Schistura pumatensis Nguyen X. K. et Nguyen H. D. sp. nov. Holotype: PM020170; SL: 64.2 mm; sample in Pumat national park, Nghean province. Paratype: 5 PM020171, SL: 59.6 mm; PM020172, SL: 58.1 mm; PM030173, SL: 54.8 mm; PM020174, SL: 55.2 mm; PM020175, SL: 55.7 mm. Same data as holotype. Diagnosis: the new species distinguished from all other species of genus in Southeast Asia by following combination characters: snout pointed, outer rostral barbel not reaching margin of orbital, body slender with small embred scales except abdomen. Description: see figures 1 and 2 for appearance and morphometric data are given on table 1. Small size, elongate body: depth 14-16.5%SL, caudal peduncle slender, depth 11.5-13.6%SL, 1.18-1,4 times in length. Head short, lateral length 21.2-23.7%SL, eye diameter 3.6-4.7%SL, located dorsally and interorbital width 5.6-6.9%SL. Caudal peduncle 1.18-1.40 longer than its deep, its depth 11-13.6% SL. Dorsal fin origin slightly in front of ventral fin origin, both lip fleshy, upper lip notched medially. Dentiformis present. Lower jaw not incision. Pectoral fin reaches 1/3 of the distance to base pelvic fin. Auxiliary pelvic lobe present but reduced. Pelvic fin just reaches anus. Caudal fin forked, margin round. Lateral line complete. Dorsal crest on caudal peduncle absent. D = 3 - 4. 7; A = 2.5; P = 1. 9 - 10; V = 1. 5 - 6, C = 5 + 14. Colour pattern: body with 14-17 black bar, as wider or thinner than interspaces, quite regularly set. Black bar at caudal - fin base complete. Dorsal fin with one black spot in simple dorsal ray. Remarks: this species near with S. bolavenensis Kottelat, S. chapaensis Rendalh but distinguished from them by branched caudal ray, color pattern, pelvic fin and pectoral fin ray, anus situation. More detail see table 2. Distribution: Khe Bu stream in Pumat national park belonging to Lam river basin. Etymology: named for Pumat national park. Habitat: this species is found in a stream with rapid running water. Associated with Vanmanenia sp., Tor brevifilis.